The Ngorongoro Crater as the biggest geotouristic attraction of the Gregory Rift (Northern Tanzania, Africa) – geological heritage - Żaba, Jerzy; Gaidzik, Krzysztof (Geotourism/Geoturystyka, 2025)
The Ngorongoro Crater is the largest unflooded and not destroyed collapse volcanic caldera of the shield volcano on Earth. It attracts many visitors each year not only because of the undoubted wealth of the wildlife and breathtaking views, but also due to the geotouristic attractiveness of this definite location. The Crater is in fact a specific example of geological processes, relevant to the development of planet Earth. In a relatively small area one can observe rocks of different types and ages: Precambrian igneous and metamorphic rocks, volcanic rocks formed in the Pliocene, Pleistocene, and even nowadays, as well as sedimentary rocks, up to those currently forming within the caldera floor. The origin and development of the Ngorongoro volcano, and lately caldera, is closely related to the activity of rifting processes occurring along the Gregory Rift, belonging to the East African Rift System. It represents one of the three arms of the Afar triple junction associated with the located here hotspot. Due to the geotouristic attractiveness, as well as a richness of living nature and archaeological sites with discoveries of our ancestors, which illustrate an important stage in the history of mankind, the area of the Ngorongoro Crater was designated a UNESCO World Cultural and Natural Heritage.